Roundtable discussion on homegrown theorizing - GÖZEN, RAMAZAN (My University, 2018)
I want to raise some preliminary questions to open this roundtable discussion, and I hope we will have an extensive and very engaging discussion. First of all, "Is there a need for post-Western theory?" It is somewhat off-putting that we still have to ask such existential questions. Moving on from there, “Can there be a post-Western theory?"; "Can IR theory be widened to include global alternative voices?"; "How can local IR communities engage with IR theory?"
Keywords: Homegrown Theorizing; post-Western theory; IR community; non-Western IR